Optimalisasi Pelaksanaan Pre dan Post Conference Keperawatan dalam Upaya Penerapan Model Praktik Keperawatan Profesional di Ruang Rawat Inap - Hendry Kiswanto Mendrofa; Dwi Astuti; Elisabeth Bre Boli; Zusana A. Sasarari; Oktliana Pasangka (I-Com: Indonesian Community Journal, 2025)
Structured nursing conferences, both pre and post, can contribute to improving patient outcomes. Conferences have been shown to enhance patient safety in care units compared to teams that do not conduct similar conferences. This activity was carried out from April to August 2024. The partners in this activity were nurses in the inpatient ward. The results of this activity included the achievement of several outcomes, such as the appointment of responsible individuals for conferences in each room, the development of shared conference techniques, and the implementation of pre and post-conferences led by the team leader/primary nurse. The socialization results also demonstrated that the conference optimization program in the Inpatient Ward of Bhayangkara Level II Hospital Jayapura successfully improved nurses' understanding and skills. Pre-conference activities allowed nurses to better plan care and align perceptions within the team, while post-conference provided space for evaluation and reflection, which are essential for continuous improvement.